Text-Free UI: Prospects for Social Inclusion - Thies, Indrani Medhi; Kuriyan, Renee (IFIP 9th International Conference on Social Implications of Computers in Developing Countries, 2007)
This paper examines the constraints that mediate the ability of individuals in developing country contexts to benefit from Information and Communication Technologies (ICTs). We identify social constraints, such as low levels of education and literacy rates, as making it difficult to access ICTs. We outline an innovative approach to address these constraints with a text free user interface (UI) design of an application for the illiterate population. We apply this text free UI to the case of a problem that ICTs hold the potential to influence—informal domestic labor markets in Bangalore, India. We examine the potential of the text free UI application and present preliminary results from user testing. These tests examine whether individuals without prior computer skills and low literacy levels could successfully navigate and access employment information. We flag challenges in promoting access to ICTs with this application, given the multiplicity of ways in which people derive benefits from technologies, the difficulties in formalizing labor relations and informal dissemination of information.